2015
DOI: 10.1111/age.12277
|View full text |Cite
|
Sign up to set email alerts
|

Two mutations in the 5′-flanking region of theKITLGgene are associated with litter size of dairy goats

Abstract: In this study, Xinong Saanen (SN) and Guanzhong (GZ) dairy goat breeds were used to detect single nucleotide polymorphisms (SNPs) in the 5'-flanking region of the KITLG gene by DNA sequencing and primer-introduced restriction analysis-polymerase chain reaction. Two novel SNPs (g.13090G>T and g.13664C>A) were identified (GenBank Accession no. KM658964). Furthermore, g.13090G>T and g.13664C>A loci were closely linked in SN and GZ breeds (r(2) > 0.33). Association analysis results showed that g.13090G>T and g.136… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Interestingly, four genes show pleiotropic effects and have been related to phenotypic effects in several livestock species. KITLG has known associations with neural stem cell systems 36 , coat color in mammals 37 , and on litter size in goats 38 . HMGI-C is a major candidate for dwarfism in chickens 39 and MTMR7 is involved in fatty acid composition in pigs 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, four genes show pleiotropic effects and have been related to phenotypic effects in several livestock species. KITLG has known associations with neural stem cell systems 36 , coat color in mammals 37 , and on litter size in goats 38 . HMGI-C is a major candidate for dwarfism in chickens 39 and MTMR7 is involved in fatty acid composition in pigs 40 .…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, nine SNPs in six genes were strongly linked with sheep litter size, confirming their genetic roles in regulating sheep litter size. Previous research found two SNPs in KIT [9] and ten SNPs in KITLG were significantly associated with goat litter size [10,11,12,13]. A mutation in ADAMTS1 was associated with pig litter size [19].…”
Section: Discussionmentioning
confidence: 99%
“…Two single nucleotide polymorphisms (SNPs) in KIT were linked with goat litter size [9]. Similarly, ten loci in KITLG were significantly associated with goat litter size [10,11,12,13]. ADAMTS1 and NOG were crucial for ovulation [14,15,16,17,18] and a mutation in ADAMTS1 was notably linked with litter size in a new Qingping female line [19].…”
Section: Introductionmentioning
confidence: 99%
“…Using Ensembl to annotate related SNPs, we found a total of 68 genes around signi cant peaks, and identi ed 32 candidate genes associated with egg production according to their functions (Table 3). Some genes such as NELL2, KITLG, GHRHR, NCOA1, ITPR1, GAMT, and CAMK4, which have been proved to be related to egg production, litter size, or reproductive traits, are worth a deeper exploration [19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Genome Wide Association Studymentioning
confidence: 99%